Methodology for Measuring Distortions to Agricultural Incentives - Anderson, Kym; Kurzweil, Marianne; Martin, Will; Sandri, Damiano; Valenzuela, Ernesto (World Bank, Washington, DC, 2017)
This paper outlines the methodological issues associated with the task of measuring that actual delivered direct protection or taxation to individual agricultural industries, as well as the direct protection or anti-protection to non-agricultural sectors. It begins with a guide to what elements in principle could be measured. There are two key purposes of the distortion estimates being generated by this project are: 1) to provide a long annual time series of indicators showing the extent to which price incentives faced by farmers and food consumers have been distorted directly and indirectly by own-government policies in all major developing, transition and high-income countries, and hence for the world as a whole; and 2) to attribute the price distortion estimates for each farm product to specific border or domestic policy measures, so they can serve as inputs into various types of partial and general equilibrium economic models for estimating the effects of those various policies on such things as national and international agricultural markets, farm value added, income inequality, poverty, and national, regional and global welfare.